(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The present work deals with the formulation and evaluation of mucoadhesive microspheres containing glycyrrhetinic acid. Mucoadhesive microspheres were prepared by single phase emulsification method and heat stabilization method. Chemical stabilization appeared as fast and simple technique for producing glycyrrhetinic acid loaded microspheres. Microspheres prepared by this method produced sufficient production yield, high drug encapsulation efficiency and reproducibility. Among the different formulations, microspheres with drug - polymer ratio of 1:1 (C1) was found to have the maximum mucoadhesive property as well as in vitro and in vivo drug release property. Therefore, it could be considered as the best formulation. Bangladesh Pharmaceutical Journal 18(1): 30-37, 2015